Efficacy and safety of various Intravenous Methylprednisolone regimens in Moderate to Severe Thyroid Eye Disease: A systematic review - Ankita Aishwarya; Divanshi Shrivastava; Adarsh Kumar Singh; Rachna Agrawal (Indian Journal of Ophthalmology)
This systematic review aims to assess the efficacy and safety of various intravenous methylprednisolone (IVMP) protocols for treating active moderate to severe thyroid eye disease (TED) and to find the most effective regimen with the least side effects. We conducted a comprehensive literature search adhering to PRISMA guidelines across PubMed, Medline, Embase, Web of Science, and Scopus databases from March 2008 to March 2024 to find relevant studies. Included studies were randomized controlled trials (RCTs), nonrandomized trials, cohort studies, case–control studies, case series, and case reports in English, investigating IVMP usage in adults with active moderate to severe TED. Outcomes focused on disease activity, exophthalmos improvement, diplopia resolution, recurrence, need of additional treatment, and associated adverse events. Of the 274 screened articles, 15 were included, involving 1065 participants. There were six RCTs (two multicentric), six retrospective studies, and three prospective case series from March 2008 to March 2024. Regimens were categorized into low dose (LD) ≤ 2.5 g, medium dose (MD) >2.5 g to 4.5 g, and high dose (HD) >4.5 g, with intervals of daily, weekly (most common), and monthly, over 4 to 26 weeks, typically 12 weeks. The MD (4.5 g) regimen was the most common followed, and it significantly improved Clinical Activity Score and quality of life with low side effects. The main limitations of this study are the heterogeneity of included studies, duration of follow-up, and IVMP regimens, which may affect the comparability and generalizability of the results. The weekly IVMP (4.5 g) regimen optimally treats moderate to severe TED. However, future research should focus on large-scale trials to determine the optimal IVMP regimen while addressing variability in managing recurrence, additional treatments, and the timing of rehabilitative surgeries.